Analisis Erosi lahan Pada Lahan Revegetasi Pasca Tambang - Novitasari Novitasari (Universitas Lambung Mangkurat, 2006)
Reclamation with revegetation is one of the ways to repair of environment which have been strived by some opened mining. This revegetation with plant meant to return land condition originally or come near original condition. The objective of this research is to identify land erosion at the reclamation land after opened mining.In this research obtained by accelerated erosion in farm region of revegetation Paringin for 168.45 ha is 545.3409 ton/year which including at erosion danger classification class I that isn’t danger condition. Erosion of revegetation at Tutupan for 50.54 ha is 4418.409 ton/year that mean as danger erosion included at class II classification that is more danger condition than at Paringin, but something that had been consideration was big bank slide.